Use of distilled Monoglyceride as a stabilizer for peanut butter - Dela Cruz, Marithris Gabriel (2000)
ABSTRACT The effects of roasting time, level of stabilizer, distilled monoglyceride Type P(V), and conditioning process on the extent of oil separation in butter were studied. The longer roasting time brought about higher percent oil separation, implying the need for higher level of stabilizer has significant effect on oil separation in peanut butter. At least 1% of distilled monoglyceride Type P(V) is recommended for incorporation to peanut to prevent oil separation.